Frequency of Observed Side Effects of "Sputnik V" Vaccine in Vaccinated People in Ardabil Province , 2021 - Saeed Mashahadi; Shahram Habibzadeh; Gholamreza Hamidkholgh; Amirahmad Arabzadeh; Elham Safarzadeh (Journal of Ardabil University of Medical Sciences)
Background: Severe acute respiratory syndrome coronavirus type 2 (SARS-COV2) caused more than one million deaths in the first 6 months of the pandemic and caused huge economic and social problems internationally. An effective vaccine is certainly essential to prevent further deaths. One of the vaccines used in the control and prevention of the disease was the Sputnik V vaccine, and in this study, the side effects of the Sputnik V vaccine in vaccinated individuals in Ardabil province were evaluated. Methods: In this retrospective descriptive cross-sectional study, the side effects observed in individuals vaccinated with the "Sputnik V vaccine" in the first and second doses were examined. Demographic information such as age and gender, history of drug use, general side effects including respiratory, gastrointestinal and neurological side effects and local side effects such as pain, swelling, redness, muscle spasms, as well as the time of onset of side effects and the duration of side effects were recorded for all vaccinated individuals. After collection, the data were analyzed using statistical methods. Results: Among general complications, body aches were the most common with 65.4% and palpitations were the least common with 1.71%. In terms of respiratory complications, sore throat and burning sensation in the throat were the most common with 8.3% and runny nose was the least common with 3.9%. Among gastrointestinal complications, nausea was the most common with 13.4% and vomiting was the least common with 2.0 %. In terms of local complications, injection site pain was the most common with 50.5% and armpit pain on the same side of the injection was the least common with 3.9%. Conclusion: Side effects of the Sputnik V vaccine were usually mild to moderate and acceptable and tolerable.